2016
DOI: 10.1016/j.ccell.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

KLF4 Is Essential for Induction of Cellular Identity Change and Acinar-to-Ductal Reprogramming during Early Pancreatic Carcinogenesis

Abstract: SUMMARY Understanding the molecular mechanisms of tumor initiation has significant impact on cancer early detection and intervention. To define the role of KLF4 in pancreatic ductal adenocarcinoma initiation, we used molecular biological analyses and mouse models of klf4 gain- and loss-of-function and mutant Kras. KLF4 is upregulated in and required for acinar-to-ductal metaplasia. Klf4 ablation drastically attenuates the formation of pancreatic intraepithelial neoplasia induced by mutant KrasG12D, whereas upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
110
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(121 citation statements)
references
References 62 publications
(92 reference statements)
2
110
0
2
Order By: Relevance
“…Although the relationship between ER stress and ADM is not well understood, a recent report suggests that ER stress resulting from perturbation of basal autophagy via loss of ATG7 is associated with spontaneous activation of ADM in a mouse model (42). ADM is critical for the initiation of pancreatic tumorigenesis (5,32). In the PKC acinar cells, GRP78 was highly elevated, suggesting that it could play a role in ADM under oncogenic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between ER stress and ADM is not well understood, a recent report suggests that ER stress resulting from perturbation of basal autophagy via loss of ATG7 is associated with spontaneous activation of ADM in a mouse model (42). ADM is critical for the initiation of pancreatic tumorigenesis (5,32). In the PKC acinar cells, GRP78 was highly elevated, suggesting that it could play a role in ADM under oncogenic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting evidences surprisingly uncovered the fact that KLF4 may have an ambivalent role in tumorigenesis in a tissue-specific manner. Actually, KLF4 acts as a tumor suppressor in colon, 13 gastric, 14 esophageal, 15,16 bladder 17 and lung cancer, 18 whereas in pancreatic 19 and breast cancer, 20,21 KLF4 is believed to function as an oncogene. For example, KLF4 is a key regulator in the initiation of premalignant intraepithelial neoplasia by mutant Kras in pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, KLF4 is a key regulator in the initiation of premalignant intraepithelial neoplasia by mutant Kras in pancreatic cancer. 19 Owing to its importance in physiological and pathological processes, KLF4 is critically regulated on different levels. Studies in recent years gradually unveiled the underlying mechanism of KLF4 regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Lo et al [6] reported that the expression of underglycosylated mucin 1 antigen varied from the PanIN stage to the late stages of the disease. Krüppel-like factor 4 is upregulated in PanIN and is essential for acinar-to-ductal metaplasia in the early stage of pancreatic carcinogenesis [7].…”
Section: Introductionmentioning
confidence: 99%